Isolation and characterization of an Escherichia coli mutant affected in the regulation of adenylate cyclase. - Guidi-Rontani, C (1981)
A mutant, cyaR1, affecting regulation of adenylate cyclase expression or activity is described. It was obtained as a thermoresistant revertant of a strain harboring a thermosensitive transcription termination factor, rho (rho-15). This mutant failed to synthesize adenosine 3',5'-phosphate and exhibited a carbohydrate-negative phenotype. A secondary mutation at the crp locus (crpC) restored the ability of the mutant to synthesize adenosine 3',5'-phosphate, enabled the expression of catabolite-sensitive operons, and conferred on the strain an extreme sensitivity to catabolite repression. In addition, we showed that the crpC mutation restored the pleiotropic carbohydrate-positive phenotype even in a delta cya background. We interpret this to mean that the adenosine 3',5'-phosphate receptor protein regulates negatively either the activity or synthesis of adenylate cyclase and that the cyaR1 mutation is either in a regulatory protein or a regulatory site of adenylate cyclase.